The Inactivation of Factor VIII in Vitro - Stibbe, J; Hemker, H. C; Creveld, S. v (Thrombosis and Haemostasis, 1972)
When normal citrated plasma is stored at 37° C and pH 7.8 the factor VIII activity drops to about 50% of its initial value during the first 8-12 h. In the following 4 days practically no further drop in activity is found. If the logarithm of the factor VIII activity is plotted against time a curve is obtained which can be described as biphasic. To explore the underlying mechanism of this phenomenon the influence of temperature, pH, Ca++ concentration and some other clotting factors was investigated. Between temperatures of 21° C and 45° C the inactivation of factor VIII was biphasic, the decrease of factor VIII being faster in both phases at higher temperatures. The inactivation at these temperatures showed a Q10 of about 2. At 52° C nearly all factor VIII activity disappeared within 8 h. Possibly the precipitation of fibrinogen at this temperature is of influence. Between pH 6.4 and 8.5 the decrease in factor VIII in the first phase was obviously slower at lower pH and the level of the second phase maintained at a higher factor VIII activity. No alteration of the normal inactivation pattern was seen in plasma from patients with congenital deficiencies of factors XII, IX or V or in normal plasma adsorbed with BaS04 which has factors II, VII, IX and X markedly decreased, nor was there any difference between platelet rich and platelet poor plasma. Low calcium concentrations (Resinplasma) markedly increased the rate of inactivation in the first phase, but did not influence the second phase.Four hypotheses are given to explain the biphasic inactivation of factor VIII: a) The presence of an inactivating substance in the first phase or a stabilizing factor in the second phase of factor VIII inactivation. b) The existence of two independent substances with factor VIII activity with different inactivation rates. c) Reversible denaturation of factor VIII in one or more steps. d) Factor VIII exists in plasma in two interdependent molecular forms. It is discussed that in view of the results of the experiments hypotheses a and b are not very likely. At present we cannot differentiate experimentally between c and d.